2011
DOI: 10.1136/bcr.09.2010.3303
|View full text |Cite
|
Sign up to set email alerts
|

Development of frontotemporal dementia in a case of bipolar affective disorder: is there a link?

Abstract: The authors present the case of a 68-year-old lady with a 35-year history of bipolar affective disorder (BPAD) type I, who developed frontotemporal dementia (FTD). Description of the psychopathology is illustrated with examples of patient's writings in order to demonstrate cognitive abilities at different stages. The diagnosis is supported by MRI and SPECT scans. The authors discuss the difficulties in differentiating the clinical presentation of chronic BPAD and FTD and examine the evidence for two important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…There appears to be an increased risk of bvFTD and nfvPPA before age 60 in those with BD, with documented cases of patients with a lifelong diagnosis of BD evolving to these frontotemporal degenerations. 20 22 In these patients, there may be a shared genetic predisposition to both BD and bvFTD, as previously noted from C9orf72 mutations. 23 Investigators have reported C9orf72 mutations in patients with BD preceding bvFTD, with possible genetic expansion from BD to bvFTD.…”
Section: Discussionsupporting
confidence: 53%
“…There appears to be an increased risk of bvFTD and nfvPPA before age 60 in those with BD, with documented cases of patients with a lifelong diagnosis of BD evolving to these frontotemporal degenerations. 20 22 In these patients, there may be a shared genetic predisposition to both BD and bvFTD, as previously noted from C9orf72 mutations. 23 Investigators have reported C9orf72 mutations in patients with BD preceding bvFTD, with possible genetic expansion from BD to bvFTD.…”
Section: Discussionsupporting
confidence: 53%
“…A possible link between bipolar disorder and bvFTD has also been suggested by case reports on patients presenting with manic symptoms as a first manifestation of bvFTD 28 , 29 and patients with a lifetime diagnosis of bipolar disorder evolving into bvFTD. 30 , 31 This large clinical overlap in social cognition, executive disturbances, and behavioral profiles might be explained by the involvement of common functional neuroanatomical networks. 32 34 …”
Section: Discussionmentioning
confidence: 99%
“…The initial presentation in both generations is bipolar disorder, suggesting an etiological relationship with the C9ORF72 repeat expansion. Published examples of individuals with bipolar disorder who later developed FTD have not included genetic characterization . Intergenerational expansion of repeated elements in other genes is associated with genetic anticipation and increased disease severity in successive generations .…”
Section: Discussionmentioning
confidence: 99%